Evaluating the dentistry program in Iran using the context, input, process, and product (CIPP) model: a comprehensive analysis - Babadi, Fatemeh; Esfandiari, Misagh; Cheraghi, Maria (Frontiers in Medicine, 2024)
Introduction Attaining a commendable level of quality in an educational program is not just important but imperative. Hence, this study was undertaken to assess the quality of the general dentistry program for students in Iran, utilizing the comprehensive Context, Input, Process, and Product (CIPP) evaluation model. Methods This cross-sectional study was carried out among dentistry students in the 5th to 13th semesters at Ahvaz Jundishapur University of Medical Sciences in Ahvaz, Iran. Data collection for this research utilized a questionnaire designed in alignment with the CIPP Evaluation Model. The perspectives of students were sought in assessing the four domains of context, input, process, and product. Statistical analysis of the data was conducted using ANOVA and T-test methods. Results The mean scores of the educational program were as fallow: Content (2.76 ± 0.58), input (2.71 ± 0.65), process (2.51 ± 0.68), and product (3.31 ± 0.68). Overall, the quality of dentistry program was undesirable in all dimensions. Among these dimensions, “product” had the highest mean, while “process” had the lowest mean score. Conclusion The results of this study indicate that the general dentistry educational program were Undesirable in all domains. The CIPP evaluation framework assists decision-makers and policymakers in determining the continuation or renewal of a training program by identifying its strengths and weaknesses.